KEPADATAN DAN KEANEKARAGAMAN JENIS GASTROPODA SAAT MUSIM TIMUR DI EKOSISTEM MANGROVE, PANTAI KEMBAPI, MERAUKE - Modesta Ranny Maturbongs; Novel Novie Ruata; Sisca Elviana (Universitas Musamus, Merauke, Papua, 2017)
This study aims to determine the density, diversity and dominance types of gastropods in mangrove areas in Kembapi Beach also the associations with physical-chemical waters parameters. The sampling method using a fixed transect lines combined with 1x1 quadrant m². Analysis data using gastropod species density index, Shannon-Wiener diversity index, Margalef species richness index and Simpson dominance index. This research founds that the gastropods consist of two sub-classes, 4 orders, 5 families, 6 genera and 9 species. The highest percentage is Nerita albicilla (19%) and Terebralia palustris (17%). The highest species density obtained from Nerita albacilla 26.6 ind / m2 and the lowest of Nerita lineata of 1.4 ind / m2. Gastropod species diversity index of 2.03. Species richness index value of 0,967. Gastropod species dominance value of 0.14. The second value of this index shows the diversity in the medium category and condition stable community mindless and no species gastropods dominate.